ANALYSIS OF THE TRADITIONAL ARTS AND CRAFT INDUSTRY SECTOR IN ORDER TO IMPROVE THE SUSTAINABLE DEVELOPMENT OF TOURISM IN MONTENEGRO - Janković, Đorđina; Govedarica, Aleksandra (The Business of Tourism, 2024)
Tourism sector in Montenegro, despite craft treasury, has not recognized the importance of its valorisation. Therefore, the purpose of this paper is to examine potential problems and weaknesses of craft sector, to explore artisans willingness to participate in sustainable tourism, and to provide solutions for entering the industry. The goal is to examine the state of craft sector, but also the attitude towards crafts valorization, to identify obstacles and create recommendations, in order to improve sustainable tourism development in Montenegro. The paper includes secondary and primary research, whereby the secondary research will be based on data of available bibliographic units, while the primary research will be based on the processing of data collected through survey, and refers to the analysis of Montenegrin craftsmen and employees in cultural institutions, regarding the current state of artisanal production. The results show a low participation of crafts in tourism, but also great interest for changes. The problems that artisans face are recognized, and the results show that there is lack of vision and strategy of development. However, there are great potentials. The research will contribute to the inclusion of small bussineses in tourism and valorisation of neglected cultural treasures, by analyzing the current situation, barriers and providing a solution. Keywords: art, craft, culture, sustainability, culture tourism